Memori Reformasi dalam Film Dokumenter “Mosi Tidak Percaya” (2019) - Aswan Zanynu (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
After two decades have passed, the word “reformation” reappeared and was used as the name of a student demonstration in September 2019. The Corrupted Reformation Movement that occurred in almost all major cities in Indonesia was then packaged in the form of a documentary film entitled “Vote of No Confidence” (2019) in two episodes. In plain view, the action field has similarities with those that happened in 1998. By using the Entman's framing analysis method, this study intends to find the reformation memory framed in the film's content. It refers to everything in film's content (audio and visual) that bring back the issue in 1998 when the student action demanded reformation in Indonesia. The findings show that memory is implicitly displayed in speeches, interviews, and demands made by students. The House of Representatives and the Government are positioned as the cause of the demonstration. They were described as martyrs who fought for more democratic Indonesia. The memory relation between the Corrupted Reformation Movement in 2019 and the Reformation movement in 1998, was told by using reflective mode in this documentary. On the one hand, the approach succeeded in giving strong emphasis to the Corrupted Reform Movement as a very important event. But on the other hand, the absence of narrator or text to explain the footage makes it difficult to emerge memory explicitly in film content. It takes public experience and knowledge on the 1998 Reformation issue, to be able to uncover the memory connection with the 2019 Corrupted Reformation Movement in this documentary.